2022
DOI: 10.1093/ibd/izac098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Network Analyses Implicate Death-Associated Protein Kinase 3 (DAPK3) as a Key Factor in Colitis-Associated Dysplasia Progression

Abstract: Background Ulcerative colitis (UC) is a progressive disorder that elevates the risk of colon cancer development through a colitis-dysplasia-carcinoma sequence. Gene expression profiling of colitis-associated lesions obtained from patients with varied extents of UC can be mined to define molecular panels associated with colon cancer development. Methods Differential gene expression profiles of 3 UC clinical subtypes and health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Thus, the inhibition of DAPK3 may serve as a strategy for the treatment of cardiovascular diseases. 156 It was reported that DAPK3 is down-regulated in ulcerative colitis (UC), but the mechanism is unclear 157 (Table 3).…”
Section: Dapk1 In Diseasesmentioning
confidence: 99%
“…Thus, the inhibition of DAPK3 may serve as a strategy for the treatment of cardiovascular diseases. 156 It was reported that DAPK3 is down-regulated in ulcerative colitis (UC), but the mechanism is unclear 157 (Table 3).…”
Section: Dapk1 In Diseasesmentioning
confidence: 99%
“…In addition to these molecular participants, a role for DAPK3 in epithelial restitution is sensible given the molecular functions assigned to the kinase. In fact, Hippo/Wnt signaling and a molecular network of differentially expressed genes (i.e., DEGs) that included DAPK3 was uniquely identified as a determinant for colitis‐dysplasia progression (Chen & MacDonald, 2022). The results further support a potential regulatory relationship among DAPK3, YAP/TAZ, and actin cytoskeletal dysregulation in the advancement of disease from pancolitis to dysplasia.…”
Section: Defined and Emergent Roles For Dapks In Epithelial Homeostasismentioning
confidence: 99%
“…With its demonstrable involvement in key signaling pathways that could facilitate epithelial regeneration after injury, it is tempting to speculate that DAPK3 may play a role in epithelial restitution and wound healing required for the resolution of colitis. In this regard, DAPK3 was recently identified as a determinant for the progression of UC from nondysplastic to dysplastic (Chen & MacDonald, 2022). However, the precise molecular actions of DAPK3 within the context of colitis or colitis‐associated dysplasia–carcinoma have yet to be elucidated.…”
Section: Dapks and Gastrointestinal Pathologiesmentioning
confidence: 99%